Building a Dream School: Integration of Alternative Inclusion Natural Schools Education centered on Children With Special Needs Based on the Quran and the Sunnah of the Prophet - Yani Yani; Nenden Ineu Herawati (Politeknik Kampar, 2024)
Education in Indonesia is still not fully inclusive for children with special needs. Forest schools and inclusive schools offer alternative approaches that focus on holistic and inclusive learning. This research aims to explore the concept of forest school and inclusive school integration to create an innovative dream school. The research method used was qualitative with an analytic descriptive approach. Data collection involved direct observation as well as literature study from books, documents and reputable journals. After the data is collected and grouped according to the data, data analysis will be carried out by applying an analytical descriptive approach, this is to get a comprehensive and in-depth understanding of the phenomenon or concept that is the focus of this research. The results of this study indicate that the integration of forest schools and inclusive schools based on the Al-Quran and Sunnah of the Prophet offers a holistic and inclusive education model. By combining outdoor learning and an inclusive approach, children with special needs can experience a supportive and motivating learning environment, in accordance with the principles of justice and compassion taught in Islam.